(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract This study aims to identify the extent to which the criteria of the American Council for Teaching Foreign Languages (ACTFL) are included in the English language books for the fifth and sixth graders. To achieve the objective of the study, a content analysis card was prepared, where the classification of language proficiencies was divided into five main levels (beginner, intermediate, advanced, superior, and distinguished) of the four language skills (listening, speaking, reading, and writing), The content analysis card consisted of (89) indicators distributed at the four levels of language skills as follows: Listening (17), speaking (33), reading (15), and writing (26). The study sample consisted of English language textbooks for the fifth and sixth graders. The study unveiled that the listening, speaking, reading, and writing skills indicators were provided in the two books at the high-level for beginner level, followed by intermediate-level indicators, while the language proficiency indicators for all skills came within the superior and distinguished levels to a minimum or unrealized degree. Based on this result, the researchers recommend that language proficiency indicators arising from the American Council Criteria for Teaching Foreign Language at their advanced levels should be included in the textbooks for fifth and sixth graders.